Ethnic Federalism and the Political Accommodation of Diversity: An Analysis of Governance Structures in Ethiopia - Dr. Peteti Premanandam, Hassan Muhamed Moalin (Journal of Daoist Studies, 2026)
This study explores the governance system and mechanisms used to accommodate diversity in Ethiopia under the framework of ethnic federalism. The research examines how constitutional and administrative arrangements distribute political power among federal, regional, and local institutions in order to manage the country’s ethnic and linguistic diversity. Using descriptive and comparative analysis, the study reviews population distribution, regional autonomy, and institutional structures such as the House of Federation and regional governments. The House of Peoples' Representatives (HPR) is the lower chamber of Ethiopia's federal parliament and serves as the principal legislative body. Members are elected through direct elections and represent the diverse peoples, nations, and nationalities of Ethiopia. The HPR plays a significant role in accommodating diversity by ensuring political representation for different ethnic and regional groups within the federal system. Through law-making, oversight of the executive, and approval of national policies, the HPR contributes to inclusive governance and democratic participation. The institution supports Ethiopia's system of ethnic federalism by providing a platform where various communities can voice their interests and participate in national decision-making processes. As such, the House of Peoples' Representatives is an important mechanism for managing diversity and promoting political integration in Ethiopia. The findings show that Ethiopia’s federal structure is largely organized around ethnic identity, with major ethnic communities concentrated in specific regions. The system has contributed to greater cultural recognition, local self-governance, and political participation for different groups. However, the study also identifies several challenges, including regional inequalities, concerns about minority rights within regional states, and political tensions linked to ethnic-based territorial arrangements. The study concludes that Ethiopia’s model of ethnic federalism represents an important but complicated effort to balance national unity with diversity through decentralized governance and institutional power-sharing.